Polymyxins as inhibitors of polyclonal B-cell activators in murine lymphocyte cultures. - Butler, T (1977)
The polymyxin antibiotics polymyxin B sulfate and colistin methane sulfonate were examined for their ability to inhibit responses to the polyclonal B-cell activators (PBA) bacterial lipopolysaccharide (LPS), dextran sulfate (DS), pneumococcal polysaccharide (SIII), and purified protein derivative of tuberculin (PPD) in spleen cell cultures. Polymyxin concentrations of 1 and 10 microng/ml significantly inhibited both the deoxyribonucleic acid synthetic and polyclonal antibody responses stimulated by LPS, DS, and SIII. At these concentrations of polymyxins, responses to PPD and to the T-cell mitogens concanavalin A and phytohemagglutinin were not affected. Inhibition was not caused by a generalized lymphocyte toxicity. After dialysis of LPS-polymyxin and DS-polymyxin mixtures, the PBA preparations showed decreased mitogenic activity. Thus, the polymyxins probably interacted directly with the LPS and DS molecules. The mitogenic response to DS was more significantly inhibited than the response to a nonsulfated dextran. The cationic property of the polymyxins probably allows attachment to negatively charged groups in the mitogenically relevant parts of some but not all PBA molecules,, this attachment resulting in the loss of PBA activity.